Consumer perception towards IBM PC’s in Bangalore City (International Journal of Food and Nutritional Sciences, 2022)
The information handling is very important to everybody, whether he is an individual or a organization. It should be handled very carefully and accurately. To handle information at all levels computer are the main tools to process, store and can be done everything through computers. Individual uses computer to store the data to maintain some sort of confidentiality. Business firms use computers to process information at all the levels to do work faster and accurately. It is reducing the burden of manpower in the organizations. Customer is a king in any business organization. Everything happens at his wish and will. He has wide range of expectations about any product. He will be satisfied, if all his expectations are met. This paper deals with consumer perception on pc’s and it consider all the factors which are connected with perception factor.